Impact of retropharyngeal adenopathy on distant control and survival in HPV-related oropharyngeal cancer treated with chemoradiotherapy. Issue 1 (July 2015) - Samuels, Stuart E.; Vainshtein, Jeffrey; Spector, Matthew E.; Ibrahim, Mohannad; McHugh, Jonathan B.; Tao, Yebin; Schipper, Matthew; Worden, Francis; Eisbruch, Avraham
Abstract Purpose Retropharyngeal adenopathy (RPA) is poor prognostic factor in head and neck (HN) cancer. However, the prognostic significance of RPA in Human Papillomavirus-related (HPV+) oropharyngeal cancer (OPC) is unknown. Patients and methods 185 patients with HPV + OPC were assessed. Pre-therapy images reviewed by a HN radiologist to determine presence of RPA. Doses to the RPAs were determined from treatment plans. Outcomes analyzed using Kaplan–Meier method, log-rank tests, and correlations determined using Spearman's rank analyses. Results 29 (16%) of the HPV + patients had RPA. At median follow-up 49 months, 5-year overall survival (OS), failure-free survival (FFS) and distant failure-free survival (DFFS) were 57% vs. 81% (P = 0.02), 63% vs 80% (P = 0.015) and 70% vs 91% (P = 0.002) for patients with/without RPA, respectively. No differences observed in local/ regional control rates, exceeding 90% in both groups, and No RPA recurrences were observed. In multivariable analysis, stages T4 or N3, and RPA, were independently, statistically significantly associated with both OS and distant failure, while N2c, age, disease site, and smoking status, were not. Conclusion RPA in HPV + OPC is an independent prognostic factor for distant failure, translating into worse OS. Patients with RPA may not be suitable candidates for trials of systemic treatment de-escalation.